The economic aspects of organic farms selling their products to organic or conventional market - Zuzana Fuksová; Iveta Bošková; Jana Hlaváčková; Marek Novák (Agricultural Economics (AGRICECON))
Organic farming is a topic often discussed in the scientific community and public space. The current European policy strongly supports the enhancement of organic farming concerning the environment, sustainability, and social aspects. It is generally assumed that a lower intensity of production, yields, livestock utility, fertilisation, and total costs should be compensated by premium prices, subsidies, or higher economic performance. Research revealed that achieving premium prices for organic products on the market is not obvious for organic farmers as some organic commodities have been sold on the conventional market. Our study focused on the price difference reached by the sample of farms on the organic and conventional markets for two organic commodities (winter wheat and milk) and the farm's economic results. We combined and compared data from two unique databases on organic farming in the Czech Republic. We used the statistical methods of ANOVA and regression for analysis. We found the difference between evaluated market prices. Price variability is wide in both types of organic and conventional markets but the influence of the prices on farm performance was not significant.